1.6k views
5 votes
8) Solve 4^(x - 2)= 8^6

A)5

B)8

C)10

D)11

User Kiwimoisi
by
5.9k points

2 Answers

3 votes

Answer: OPTION D

Explanation:

You need to remember the following:


a^x=a^y\\x=y

Then, you must descompose 4 and 8 into their prime factors:


4=2*2=2^2\\8=2*2*2=2^3

Rewriting the expression:


2^(2(x-2))=2^(3(6))

Now you get:


2(x-2)=3(6)

Finally, you must solve for the variable "x".

Therefore, you get the following result:


2x-4=18\\2x=22\\x=11

User Semenchikus
by
5.9k points
4 votes

For this case we have the following equation:


4 ^ {(x-2)} = 8 ^ 6

We must create equivalent expressions in the equation, so that they have equal bases:


2 ^ {2 * (x-2)} = 2 ^ {3 * 6}

If the bases are the same, then the two expressions are only equal if the exponents are equal:


2 (x-2) = 3 * 6\\2 (x-2) = 18\\2x-4 = 18\\2x = 18 + 4\\2x = 22\\x = \frac {22} {2}\\x = 11

Answer:


x = 11

Option D

User Gan Yi Zhong
by
5.6k points